Pengaruh Suhu Ekstrusi dan Komposisi terhadap Karakteristik Filamen Biokomposit PLA/Hidroksiapatit untuk Aplikasi Ortopedi Berbasis 3D Printing - M. Mukaddam Alaydrus; Wahyudin; Susi Rahayu; Dyah Purnaning; Maz Isa A.A; Muh. As’ad Hamzah; Hurnah; Ahmad Taufik S (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
Fused deposition modeling-based 3D printing requires biomaterial filaments with stable dimensions, uniform surface texture, and adequate mechanical properties for orthopedic applications. This study examined the effects of extrusion temperature and PLA/hydroxyapatite composition on the characteristics of biocomposite filaments. Hydroxyapatite was synthesized from Pinctada maxima pearl shell waste through wet precipitation, mixed with PLA, and processed using a single-screw extruder. PLA extrusion temperatures were varied at 120, 125, 130, and 135°C, while PLA/hydroxyapatite compositions were 100:0, 95:5, 90:10, and 85:15. The results showed that increasing temperature improved surface texture and diameter stability; 135°C produced the smoothest filament surface with a diameter of 2.080 mm, whereas the highest mechanical properties of PLA were obtained at 130°C. In the biocomposite filaments, all diameters remained within the standard range for 3D printing. The PLA/hydroxyapatite 90:10 composition showed the best performance, with a density of 1.470 g/cm³, tensile strength of 4.692 MPa, elastic modulus of 1426.500 MPa, and elongation of 0.173 mm. Adding 15% hydroxyapatite reduced quality due to particle agglomeration. Further validation is required.